Modernity in Iran and Turkey: Patterns and Problems - Younes Nourbakhsh (Religious Inquiries, 2020)
Modernity implies ways of social and organizational life that began to improve in seventeenth-century Europe and gradually developed into the rest of the world. Due to its unanimous and progressive rationality, modernity has been highly influential in social, cultural, and political spheres, both in the West and among Muslim nations. Nations’ encounters with modernity have not always followed consistent patterns, and every country has had a unique experience of its own. Iran and Turkey are countries whose modern experience bears similar characteristics but gave way to entirely different outcomes. Modernization in both countries accelerated the growth of political and philosophical opposition, including that of the Islamist movement that regarded modernity as the enemy of national culture and religious values. Iran and Turkey made different choices and formed different fronts against modernity. This article is a historical sociology of modernity in Iran and Turkey that evaluates the divergent experience in each country, applying Eisenstadt’s theory of Multiple Modernities to examine the changes and outcomes of modernity in them.